User Experience Game Arknights: Sebuah Penerapan Metode Cognitive Walkthrough - Andri Daviano; Reni Aryani; Daniel Arsa (Jurnal PROCESSOR, 2024)
Every product requires an optimal user experience to ensure user comfort and effective interaction with the product. This research uses the Cognitive Walkthrough method to evaluate the user experience in the Arknights game, a mobile game that won the "Best Innovative Game" award at the Google Play Best Of 2020 awards. The Cognitive Walkthrough method is a user experience evaluation method where respondents are asked to work on scenario-based tasks that have been prepared by researchers. This method will evaluate step by step in a product, to find problems that make users uncomfortable. This evaluation aims to identify potential issues that may disrupt the user experience, especially for new users. The respondents in this study were 5 people with the main criteria being a gamer but had never played the Arknights game. The evaluation results show that Arknights has a high level of comfort overall, with most problems being minor and not affecting the main functions of the game. The issues identified were mostly related to specific in-game tasks, such as upgrading operators and change assistants, as well as basic in-game features. However, these issues are minor and do not hinder the gaming experience significantly. This evaluation shows that Arknights is a game that is easy to play and enjoy, especially for new users.